Frontiers in Soil and Environmental Microbiology - Mishra, Bibhuti Bhusan, 1938-; Nayak, Suraja Kumar (Milton : CRC Press LLC, 2020)
Soil harbours a wide range of microorganisms with biotic potentials which can be explored for social benefits. The book Frontiers in Soil and Environmental Microbiology comprises an overview of the complex inter-relationship between beneficial soil microbes and crop plants, and highlights the potential for utilisation to enhance crop productivity, bioremediation and soil health. The book focusses on important areas of research such as biocide production, pesticide degradation and detoxification, microbial decay processes, remediation of soils contaminated with toxic metals, industrial wastes, and hydrocarbon pollutants. Features Presents the state of the art of microbial research in environmental and soil microbiology Discusses an integrated and systematic compilation of microbes in the soil environment and its role in agriculture and plant growth and productivity Elucidates microbial application in environmental remediation Explores advanced genomics topics for uncultivable microbes of soil
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Environmental Science; SCIENCE / Life Sciences / Biology / Microbiology; SCIENCE / Life Sciences / General; Microbial ecology; Soil microbiology